SPECIFICATIONS OF «MANAGING» THE EDUCATIONAL PROCESS IN THE CONDITIONS OF DISTANCE LEARNING (EXPERIENCE OF UKRAINE) - Khilya, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
This publication focuses on the practice of implementing non-standard approaches to standardized educational processes. The involvement of students in the practical study of the possibilities of using a virtual classroom not only as a basic model for the transfer and testing of knowledge, but also to improve the emotional response and involvement in the educational process. This is due to the inclusion of art therapy technologies, its elements, and individual practice-oriented exercises in the structure of classes, which are inherently training.That is why in this publication we turned to the demonstration of the results of the survey, interviews with the participants of our classes. In particular, not only those with whom we have been working consistently and systematically for more than one year, but also those who study under other programs without the inclusion of the technologies and exercises we offer. In addition, to demonstrate the effectiveness of this method of managing the educational process, we propose to review the work with the use of the proposed inclusions when working with a «new» audience in the process of participation and presentation of the results of interaction with participants of all-Ukrainian conferences.